a placebo control study of the effect of nigella sativa fixed oil on the healing rate of recurrent aphthous ulceration - abdalli, samara M.; hadi, nasir A.; Ali, Abbas F.; waiz, makram M. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: